Training on implementation of sex education since early age for kindergarten teachers at Lubuk Basung, Agam - Rismareni Pransiska; Syahrul Ismet; Serli Marlina (Fakultas Ilmu Pendidikan UNP)
Many sexual abuses happened on children. Because of their ignorance, children did not realize that they became victims. Teachers are responsible for providing this information to children. The training aimed to provide kindergarten teachers on how to apply sex education in early childhood at schools especially in Lubuk Basung. The methods used in this training were lectures, questions and answers, concerning three materials: Urgency of Sex Education since early age, Sex education material and Implementation of Sex Education. There were several positive outcomes; Participants showed high enthusiasm on the materials taught, Participants understood the need and urgency of sex education from an early age and Participants were able to include materials for young learners in the learning activitie.